Destabilization and recuperability of oil used in the formulation of concentrated emulsions and cutting fluids - Guimarães, A. P. (2010)
Lubricants known as cutting fluids are used in the metal-mechanic industry with the function of cooling and lubricating the cutting zone. These lubricants normally have a water phase, an oil phase, emulsifying agents and additives. Once the operational capacity of these fluids has ceased, either due to biological deterioration or to overabundance of contaminants, the emulsions being used must be treated in order to adequate their effluents for discharge. This study aims to evaluate the destabilization process and recuperability of the oil used in the formulation of concentrated emulsions and cutting fluids. For this purpose, the following destabilizing factors were tested: temperature, centrifugation speed, and concentration of inorganic salts. The optimization of the process with concentrated emulsion allowed for the following most adequate condition of demulsification: temperature of  70 °C, centrifugation of 2000 rpm, and salt concentration of  2000 g /L. As for the cutting fluids, the conditions were less severe, with salt concentration around 50 g/L, and temperature of 50 °C. FTIR technique was used to determine the concentration of emulsifying agents used in the preparation of concentrated emulsions. This procedure was not carried out for the cutting fluid due to the diversity of substances present in its composition derived from the additives that either make it difficult or prevent the identification of the peaks shown in the FTIR spectra.